Comparison of effectiveness of growth hormone therapy according to disease-causing genes in children with Noonan syndrome - Kyo Jin Jo; Yoo Mi Kim; Ju Young Yoon; Yeoun Joo Lee; Young Mi Han; Han-Wook Yoo; Hyang-Sook Kim; Chong Kun Cheon (Korean Pediatric Society, 2019)
Purpose To analyze the growth response to growth hormone (GH) therapy in prepubertal patients with Noonan syndrome (NS) harboring different genetic mutations. Methods Twenty-three patients with prepubertal NS treated at Pusan National University Children's Hospital between March 2009 and July 2017 were enrolled. According to the disease-causing genes identified, the patients with NS were divided into 4 groups. Three groups were positive for mutations of the PTPN11, RAF1, and SOS1 genes. The five genes undetected (FGU) group was negative for PTPN11, RAF1, SOS1, KRAS, and BRAF gene mutations. The influence of genotype was retrospectively analyzed by comparing the growth parameters after GH therapy. Results The mean chronological age at the start of GH treatment was 5.85±2.67 years. At the beginning of the GH treatment, the height standard deviation score (SDS), growth velocity (GV), and lower levels of insulin-like growth factor-1 (IGF)-1 levels were not statistically different among the groups. All the 23 NS patients had significantly increased height SDS and serum IGF-1 level during the 3 years of treatment. GV was highest during the first year of treatment. During the 3 years of GH therapy, the PTPN11, RAF1, and SOS1 groups showed less improvement in height SDS, IGF-1 SDS, and GV, and less increase in bone age-to-chronological age ratio than the FGU group. Conclusion The 3-year GH therapy in the 23 prepubertal patients with NS was effective in improving height SDS, GV, and serum IGF-1 levels. The FGU group showed a better response to recombinant human GH therapy than the PTPN11, RAF1, and SOS1 groups.